Determination of cobalt in vegetables by flame atomic absorption spectrometry after preconcentration on activated carbon - Yaman, M; Gucer, S (My University, 1995)
An activated carbon enrichment method has been developed for the determination of cobalt in vegetables by flame atomic absorption spectrometry. The samples were dry ashed at 470°C and the ashes desolved with a mixture of nitric and perchloric acids. The metal was adsorbed on activated carbon by using 8-hydroxyquinoline and cupferron. The adsorbed cobalt was separated by elution with concentrated and 2 M (2 ml) nitric acid, respectively. The cobalt level in the clear solution was determined by flame atomic absorption spectrometry. The parameters such as pH. amount of complexing reagents, amount of activated carbon and stirring time were optimized for maximum recovery. It was found that the optimum pH ranges were 5.5-9.0 by using 8-hydroxyquinoline and 4.5-9.0 by using cupferron. The relative standard deviation was found to be 2% for cobalt concentration of 40 ?g l-1. Results for the determination of cobalt in various vegetables are given. © 1997 Elsevier Science Ltd. All rights reserved.
Keywords: cobalt; flame atomic absorption spectrometry; preconcentration on activated carbon; vegetables